Evaluating the genocidal character of the massacres against the Amhara people in Oromia region of Ethiopia - Kiremte, Henok Ashagrey (University of Pretoria, 2024)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.